The future of intermodal freight transport operations, design and policy - Konings, J. W.; Priemus, Hugo 1942- editor; Nijkamp, Peter editor (Transport economics, management, and policy, 2008)
This book explores the great challenge of increasing the scope of intermodal freight transport. In view of the current dominant role of road transport and the increasing difficulties in coping with a growing number of vehicles in an efficient and sustainable way, intermodal freight transport could be considered a viable alternative